2016
DOI: 10.1021/acs.jafc.5b05945
|View full text |Cite
|
Sign up to set email alerts
|

Germinating Peanut (Arachis hypogaea L.) Seedlings Attenuated Selenite-Induced Toxicity by Activating the Antioxidant Enzymes and Mediating the Ascorbate–Glutathione Cycle

Abstract: Selenite can enhance the selenium nutrition level of crops, but excessive selenite may be toxic to plant growth. To elucidate the mechanisms underlying the role of selenite in production and detoxification of oxidative toxicity, peanut seedlings were developed with sodium selenite (0, 3, and 6 mg/L). The effects of selenite on antioxidant capacity, transcript levels of antioxidant enzyme genes, and enzyme activities in hypocotyl were investigated. The CuZn-SOD, GSH-Px, GST, and APX gene expression levels and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…In the present study, the application of 2,4 D enhanced the activation of antioxidant enzymes under saline stress conditions, which is in line with previous studies in which natural auxin and synthetic auxin (2,4-D) stimulated the activities of antioxidant enzymes, such as SOD, CAT, and APX in wheat, maize and other plants under abiotic stress conditions 65 67 . This may suggest that enhanced antioxidant capacity under combined stress conditions may be due to 2,4-D modification in the transcription of the genes that encode antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the application of 2,4 D enhanced the activation of antioxidant enzymes under saline stress conditions, which is in line with previous studies in which natural auxin and synthetic auxin (2,4-D) stimulated the activities of antioxidant enzymes, such as SOD, CAT, and APX in wheat, maize and other plants under abiotic stress conditions 65 67 . This may suggest that enhanced antioxidant capacity under combined stress conditions may be due to 2,4-D modification in the transcription of the genes that encode antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 93%
“…GSH and AsA are directly oxidized by ROS, or indirectly oxidized via coupling reactions of the ascorbate–glutathione recycling pathway 67 , 70 . In this study, the GR activity significantly increased in the resistant cultivar compared to the sensitive one under saline stress and combined treatments, which correlates with the a higher accumulation of GSH in XS 134 cultivar compared with the ZJ 88 cultivar under the saline stress and combined treatments (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the assay of antioxidant substances, 1.0 g of cucumber leaves were homogenized in 5 mL of 1% ( w / v ) saline buffer (1% ( w / v ) PVP, 1 mmol/L ethylenediaminetetraacetic acid (EDTA)). Homogenates were centrifuged at 11,000 g for 15 min at 4 °C and the supernatants were collected to check the content of ASA and GSH [39].…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that living cells contain a large number of antioxidant enzymes and CAT and GSH‐Px production has been frequently employed to describe the cellular oxidative stress state (Wang et al., ). As shown in Figure D and 3E, cells with 24‐hr OA incubation obtained the lowest CAT and GSH‐Px production, showing the OA‐induced oxidative damage ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%